The mouse cyclophosphamide model of bladder pain syndrome: tissue characterization, immune profiling, and relationship to metabotropic glutamate receptors. Issue 3 (27th March 2014) - Golubeva, Anna V.; Zhdanov, Alexander V.; Mallel, Giuseppe; Dinan, Timothy G.; Cryan, John F.
Abstract Painful bladder syndrome/Interstitial cystitis (PBS/IC) is a chronic disorder characterized clinically by recurring episodes of pelvic pain and increased urination frequency, significantly impairing patients' quality of life. Despite this, there is an unmet medical need in terms of effective diagnostics and treatment. Animal models are crucial in this endeavor. Systemic chronic administration of cyclophosphamide (CYP) in mice has been proposed as a relevant preclinical model of chronic bladder pain. However, molecular mechanisms underlying the pathogenesis of this model are lacking. Here, we show that mice, subjected to repetitive systemic injections of CYP, developed mild inflammatory response in bladder tissue characterized by submucosal edema, moderate increase in proinflammatory cytokine gene expression, and mastocytosis. No signs of massive inflammatory infiltrate, tissue hemorrhages, mucosal ulcerations and urothelium loss were observed. Instead, CYP treatment induced urothelium hyperplasia, accompanied by activation of proliferative signaling cascades, and a decrease in the expression of urothelium‐specific markers. Metabotropic glutamate (mGlu) receptors have been implicated in chronic pain disorders. CYP administration induced differential changes in mGlu receptors mRNA levels in bladder tissue, without affecting gene expression at spinal cord level, pointing to the potential link between peripheral mGlu receptors and inflammation‐induced bladder malfunction and hyperalgesia. Taken together, these data indicate that chronic CYP treatment in mice is a model of PBS mostly relevant to the major, nonulcerative subtype of the syndrome, characterized by a relatively unaltered mucosa and a sparse inflammatory response. This model can help to elucidate the pathogenetic mechanisms of the disease.